GPS constraints on active deformation in the Isparta Angle region of SW Turkey - Tiryakioglu, Ibrahim; Floyd, Michael; Erdogan, Saffet; Gulal, Engin; Ergintav, Semih; McClusky, Simon; Reilinger, Robert (OXFORD UNIV PRESS, 2013)
We use survey and continuous GPS observations during the period 1997-2010 to investigate active deformation in the Isparta Angle region of SW Anatolia, Turkey. This region, bordered by the Fethiye Burdur Fault Zone (FBFZ) in the west and the SE extension of the Aksehir Simav Fault Zone (AKSFZ) in the east, accommodates a part of the active deformation of W Turkey. Our results show that the Isparta Angle region rotates counter-clockwise (CCW) with respect to Anatolia. Both the FBFZ and the AKSFZ are predominantly transtensional boundaries that accommodate southward motion of the Isparta region with respect to Anatolia. The FBFZ has left-lateral strike-slip behaviour along its SW segment that changes to right-lateral strike-slip along its NE extension. This change in the sense of strike-slip motion is accommodated by extension on a NW-SE striking normal fault system that is associated with the Menderes Graben system. Transtensional fault systems along the boundaries of the Isparta Angle with Anatolia are inconsistent with extrusion models for present-day southward motion. An increase in motion rates towards the Hellenic and Cyprus arc subduction systems, and CCW of the Isparta region, supports dynamic models involving active rollback of the subducting African Plate, toroidal mantle flow around the eastern edge of the subducting African slab near the Hellenic arc/Florence Rise junction, and/or gravitational collapse of the overriding Anatolia Plate.
Keywords: Satellite geodesy; Space geodetic surveys; Continental neotectonics; Dynamics of the lithosphere and mantle; Kinematics of crustal and mantle deformation; MIDDLE-EAST; KINEMATICS; EVOLUTION; DYNAMICS; BASIN; ANATOLIA; SYSTEM; FAULT; EXTENSION; SHEAR; Geochemistry & Geophysics